Disrupted serotonin system development via early life antidepressant exposure impairs maternal care and increases serotonin receptor expression in adult female offspring. Issue 6 (9th June 2022) - Unroe, Keaton A.; Maltman, Jessica L.; Shupe, Elizabeth A.; Clinton, Sarah M.
Abstract: Manipulating serotonin (5‐HT) levels in the developing brain elicits a range of effects on brain function and behavior. For example, early‐life exposure to selective 5‐HT reuptake inhibitor (SSRI) antidepressants disrupts dorsal raphe function and triggers aberrant adult behaviors such as increased passive stress coping and anhedonia. However, much less is understood about how alterations in 5‐HT signaling in early life impact outcomes in female offspring, including critical social functions such as maternal care. The present study shows that early‐life SSRI exposure disrupts adult female offspring's maternal behavior. Pregnant/postpartum female Sprague–Dawley rats were treated with the SSRI citalopram in drinking water or provided regular tap water as control. Female offspring were raised to adulthood and mated with treatment‐naïve males. Following parturition, we observed maternal behavior during portions of the light and dark phases of postnatal days (P)1–14. Relative to controls, dams with a history of early‐life SSRI exposure exhibited decreased maternal care, including diminished arched‐back nursing, reduced licking and grooming of pups, and increased behavioral inconsistency. Brains were collected from dams with and without a history of early‐life SSRI exposure to measure relative mRNA expression of select 5‐HT receptor transcripts ( 5HTR1A, ‐1B, ‐2A, ‐ 2C ) in regions involved in maternal care. Early‐life SSRI exposure augmented expression of 5‐HTR1A in the medial preoptic area and 5‐HTR1B, 5‐HTR2A, and 5‐HTR2C in the prefrontal cortex. These results demonstrate that early alterations to 5‐HT signaling through SSRI exposure may disrupt nurturing parental behaviors and 5‐HT receptor expression in affected female rat offspring.